Development of Students' Religious Character Through Positive Culture at Madrasah Ibtidaiyah - Swari, Maulida Fuji Anjas; Isnaini, I; Madum, Mohamad (Institut Islam Mamba'ul 'Ulum Surakarta, 2026)
This study aims to describe and analyze the application of positive culture in the development of students' religious character at MI Unggulan An-Nawawi Purworejo. This study used a descriptive qualitative approach. Data were collected through observation, interviews, and documentation involving 1 principal, 4 teachers, and 25 students as research informants. Data analysis was carried out using Miles and Huberman's interactive model through three stages: data reduction, data presentation, and conclusion visualization, with triangulation to ensure validity. The results of the study show that the application of positive culture included various structured religious habituation programs such as greetings and shaking hands in the morning, tadarus al-Qur'an, congregational prayers, memorization of short letters, and weekly infaq activities. The strategies used include habituation, examples, and positive reinforcement. Supporting factors for the implementation of a positive culture include the commitment of madrasah heads and teachers, support from madrasah foundations and committees, and adequate facilities and infrastructure. Inhibiting factors include the diversity of family backgrounds, the influence of the social environment and media, limited learning time, and consistency in implementation.